Determinants of incomplete immunization and factors for missed opportunities in urban Dhaka: A cross-sectional study - Zahid Hasan Khan; Shamim Ahmed; Mohammad Ashraful Amin; Md Taufiqul Islam; Faisal Ahmmed; Motaher Hossain; Muhammad Shariful Islam; Tajul Islam A. Bari; Taufiqur Rahman Bhuiyan; Firdausi Qadri; Ashraful I. Khan (PLoS ONE, 2025)
Most vaccinations in the immunization schedule need two or more doses to elicit a protective immune response. Therefore, completion of all doses is crucial for achieving the best possible immunity. The objective of this study was to investigate the factors influencing missed opportunities of polio vaccination in children between the ages of 1–3 years in urban Dhaka. In 2018, according to the immunization card records or histories from parents/guardians, we sorted1–3-year-old children from areas of Dhaka South City Corporation who were not fully immunized. Immunization records were obtained from the Expanded Program on Immunization (EPI) card or maternal recall. Reasons for non-vaccination were documented. A total of 501 children were tracked down to determine the causes of their incomplete polio doses. Determinants of incomplete immunization and factors for missed opportunities were assessed by using bivariate and multivariable logistic regression model. The households with a child who had not received all the recommended vaccines had a considerably lower monthly income (18,000 BDT; p < 0.001). In both the complete and partial vaccination groups, the average family size was five people, and the average child age was 28 months. Education level of the household head after adjustment (AOR), the odds of the event occurring decrease by 25% with primary education (95% CI: 0.66, 0.85), p-value: < 0.001). Occupation of the household head for rickshaw/van/cart puller, AOR, the odds increase even more, with the event being 3.15 times more likely for this occupation (95% CI: 1.95, 5.08) and statistical significance (p-value < 0.05). Again, for daily wager AOR, 2.16 times higher for daily wagers (95% CI: 1.35, 3.45) and statistical significance (p-value: 0.001). This study identifies sociodemographic factors that influence incomplete childhood immunization in this urban area of Dhaka. In order to improve the coverage, the identified factors need to be mitigated and policymakers should focus on enhancing community engagement, combating misinformation and increasing the accessibility of vaccination services.